The Moderation Effect of Corporate Governance Mechanisms on The Relationship Between Capital Structure and Company Performance (Empirical Study on Insurance Companies Listed on The Indonesian Stock Exchange 2019 – 2022) - Wulandari, Wike; Sudaryanti, Dwiyani; Fakhriyyah, Dewi Diah (Universitas Islam Malang, 2024)
The significance of Company Performance extends to enhancing shareholder value, boosting employee morale, solidifying industry standing, intensifying market competition, fulfilling stakeholder expectations, and adhering to regulatory standards. Enhanced performance not only elevates the prosperity of shareholders but also augments the company's overall value. This study aims to investigate the impact of Capital Structure on Company Performance, emphasizing the moderating effect of Corporate Governance mechanisms. A quantitative approach is adopted, and the research relies on secondary data obtained from the Indonesia Stock Exchange (IDX) for this correlational analysis. The analysis encompasses annual report data from financial entities within the insurance sub-sector from 2019 to 2022, incorporating 68 datasets. The selection of these samples was conducted through a purposive sampling technique. SmartPLS 3.0 was used as this investigation's analytical instrument, employing Partial Least Square (PLS) path analysis. The outcomes indicated a minimal effect of Capital Structure on Company Performance. Moreover, the research ascertained that the effect of Capital Structure, as quantified by the debt-asset ratio (DAR), on Company Performance, assessed through the Return on Assets (ROA), remains insignificant even when considering the moderating variable of Commissioner's Size. The effect of capital structure (DAR) on company performance (ROA) with board size as a moderating variable is insignificant. 4. Capital Structure (DAR) on Company Performance (ROA) with Audit Committee Size as Moderating Variable's effect is insignificant.Keywords: Corporate governance, capital structure, company performance